Studies on the Pathogenicity of Anaerobes, Especially Prevotella bivia, in a Rat Pyometra Model - H. Mikamo; K. Kawazoe; K. Izumi; K. Watanabe; K. Ueno; T. Tamaya (Hindawi Limited, 1998)
Objective: Prevotella bivia is one of the anaerobic bacteria that resides in the flora of the female genital tract. We studied the pathogenicity of P. bivia in a rat pyometra model.